Two in a bed: The influence of couple sleeping and chronotypes on relationship and sleep. An overview. (25th November 2016) - Richter, Kneginja; Adam, Sophia; Geiss, Lennard; Peter, Lukas; Niklewski, Guenter
ABSTRACT: Objective : To summarize research on couple sleeping with respect to gender-specific differences and chronotype. Methods : Systematic review of the literature. Results : Millions of adults around the world share their beds with a partner. This may be an expression of intimacy and attachment and tends to intensify romantic relationships. Yet, couple sleeping still has underestimated implications for the quality of the relationship, quality of sleep and for physical and psychological health which are not consistently positive. Implications for research and therapy are discussed. Conclusions : Despite the people involved perhaps not even being aware of their nocturnal interactions, it is important that sleeping together becomes a subject of discussion. Abbreviations: REM: rapid eye movement; QOL: quality of life; OSA: obstructive sleep apnea; CPAP: continuous positive airway pressure